2022
DOI: 10.3389/fimmu.2022.1018544
|View full text |Cite
|
Sign up to set email alerts
|

A novel necroptosis-related lncRNA signature for predicting prognosis and anti-cancer treatment response in endometrial cancer

Abstract: BackgroundNecroptosis, a form of programmed cell death, underlies tumorigenesis and the progression of cancers. Anti-cancer strategies targeting necroptosis have increasingly been shown to present a potential cancer therapy. However, the predictive utility and anticancer sensitivity value of necroptosis-related lncRNAs (NRLs) for endometrial cancer (EC) are currently unknown.MethodsEC patient gene expression profiles and the corresponding clinical information collected from The Cancer Genome Atlas were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are defined as RNA molecules that exceed 200 nucleotides and are not translated into proteins (32). These RNAs can regulate the expression of target genes by participating in epigenetic, transcriptional and post-transcriptional pathways, and are related to the proliferation, migration and invasion of various tumors, such as female reproductive or gynecological cancers (33,34).…”
Section: Lncrna Xist/mir-129-2-3p Axis Targets Ccp110 To Regulate The...mentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are defined as RNA molecules that exceed 200 nucleotides and are not translated into proteins (32). These RNAs can regulate the expression of target genes by participating in epigenetic, transcriptional and post-transcriptional pathways, and are related to the proliferation, migration and invasion of various tumors, such as female reproductive or gynecological cancers (33,34).…”
Section: Lncrna Xist/mir-129-2-3p Axis Targets Ccp110 To Regulate The...mentioning
confidence: 99%
“…Previous studies have revealed that lncRNAs are dysregulated and play diverse roles in the carcinogenesis, metastasis, and therapeutic resistance of UCEC [10] . Several lncRNA-related prognostic models have been developed to aid the clinical management of UCEC [11] , [12] , [13] . Nevertheless, the role of DDR-related lncRNAs (DRLs) in UCEC has not been comprehensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are composed of more than 200 nucleotides, shown to be increasingly involved in various malignant cancer progression ( 6 ). LncRNAs were found to be involved in UCEC cell proliferation, invasion, and metabolic changes by targeting miRNAs axis ( 7 ). Experimental study has suggested that LINC00958 regulates the function of IGF2BP3, thus participating in the tumorigenesis and progression of UCEC ( 8 ).…”
Section: Introductionmentioning
confidence: 99%